Daily Total Physical Activity and Incident Cardiovascular Disease in Japanese Men and Women: Japan Public Health Center–Based Prospective Study. Issue 15 (11th April 2017) - Kubota, Yasuhiko; Iso, Hiroyasu; Yamagishi, Kazumasa; Sawada, Norie; Tsugane, Shoichiro
Abstract : Supplemental Digital Content is available in the text.